Roll-to-roll continuous patterning and transfer of graphene via dispersive adhesion1. Issue 16 (28th April 2015) - Choi, Taejun; Kim, Sang Jin; Park, Subeom; Hwang, Taek Yong; Jeon, Youngro; Hong, Byung Hee
<x xml:space="preserve">Abstract</x> We present a roll-to-roll, continuous patterning and transfer of graphene sheets capable of residue-free and fast patterning.